Characterising independent candidates in Indonesian local politics - Dinarto, Dedi (2021)
This article examines the phenomenon of independent candidates (calon perseorangan) in Indonesia’s regional executive elections (Pilkada) to better understand why candidates run as independents and whether independent candidacy has reduced political inequality in the electoral system. In this study, we compiled candidate information using Indonesia’s General Election Commission’s (Komisi Pemilihan Umum, KPU) database as well as structured open-source searches to develop a data set and profiles of independents over three election cycles. Using this data set, we distinguished three categories of independents – partisan, non-partisan, and underdog independents – by analysing differences in power resources and motivations among the candidates. We found that contrary to public perceptions in Indonesia, independent candidacy has not helped to alleviate unequal access to political office. Successful independents are predominantly political insiders and local notables. This finding has important implications for democracy in Indonesia – we show how the inability for political outsiders to win political office harms democratic representation.